Validity and reliability of Preschool Language Scale 4 for measuring language development in children 48-59 months of age - Sidarta, Nuryani; Tulaar, Angela BM; Nasution, Amendi; Suryanto, Suryanto (Faculty of Medicine, Trisakti University, 2008)
Prevalence rates for speech and language delay have been reported across wide ranges. Speech and language delay affects 5% to 8% of preschool children, often persisting into the school years.Â A cross-sectional study was conducted in 208 children aged 48-59 months to determine the validity and reliability of the Indonesian edition of the Preschool Language Scale version 4 (PLS4) as a screening tool for the identification of language development disorders. Construct validity was examined by using Pearson correlation coefficient. Internal consistency was tested and repeated measurements were taken to establish the stability coefficient and intraclass correlation coefficients (ICC) for test-retest reliability. For construct validity, the Pearson correlation coefficient ranged from 0.151-0.526, indicating that all questions in this instrument were valid for measuring auditory comprehension (AC) and expressive communication skills (EC). Cronbachâ€™s alpha level ranged from 0.81-0.95 with standard error of measurement (SEM) ranging from 3.1-3.3. Stability coefficients ranged from 0.98-.0.99 with ICC coefficient ranging from 0.97-0.99 both of which showed an excellent reliability. This study found that PLS-4 is a valid and reliable instrument. It is easy to handle and can be recommended for assessing language development in children aged 48-59 months.